PERAN POLITIK KIAI DALAM PROSES POLITIK DI PARTAI POLITIK (Studi Kasus Peran KH. A. Haris Shodaqoh di Partai Persatuan Pembangunan) - ULIN NUHA, ULIN NUHA (Politika: Jurnal Ilmu Politik, 2012)
Abstract Since the passing of the reform party brings a lot of the principles of Islam as an ideological platform and the foundation of the party. This seems in line with the kiai activities to disseminate the teachings of Islam. Of course the inevitable happened "utilization" in the pesantren kiai leadership by politicians that carries both Islamic and nationalist principles. Practical political developments in Indonesia to bring a number of kiai involved directly or indirectly in the political scene in the country.Using kiai political aspirations of political parties in national and local level in every election. As a result, kiai faced practical political world filled with uncertainty and interests. Variety of tactics and strategies that run political campaigns of political parties usually do not forget the importance of the role of kiai as a "vote getter" in the forefront of collecting votes. Keyword : The Role of Political, Kiai, Political parties